2020
DOI: 10.1088/1361-6633/ab85ba
|View full text |Cite
|
Sign up to set email alerts
|

A review on role of tetra-rings in graphene systems and their possible applications

Abstract: Inspired by the success of graphene, various two-dimensional (2D) non-hexagonal graphene allotropes having sp 2 -bonded tetragonal rings in free-standing (hypothetical) form and on different substrates have been proposed recently. These systems have also been fabricated after modifying the topology of graphene by chemical processes. In this review, we would like to indicate the role of tetra-rings and the local symmetry breaking on the structural, electronic and optical properties of the graphene system. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 175 publications
1
43
0
Order By: Relevance
“…Due to confinement, the electronic states become less dispersive in comparison with the bulk diamond. The fully occupied states are extended in an energy interval of 21.24 eV, which is well comparable to the previously reported energy distribution of the occupied states in bulk diamond [15]. In the interval between about -22 to −10 eV below valence band, the band structure of the wire is dominated by the carbon 2s bonding interactions and represents the expected parabolic behavior with k. The higher occupied bands, based on the s-bonding of carbon 2p orbitals, start in about -8 eV at G-point from the top of the valence band.…”
Section: H-terminated Dnwsupporting
confidence: 89%
See 1 more Smart Citation
“…Due to confinement, the electronic states become less dispersive in comparison with the bulk diamond. The fully occupied states are extended in an energy interval of 21.24 eV, which is well comparable to the previously reported energy distribution of the occupied states in bulk diamond [15]. In the interval between about -22 to −10 eV below valence band, the band structure of the wire is dominated by the carbon 2s bonding interactions and represents the expected parabolic behavior with k. The higher occupied bands, based on the s-bonding of carbon 2p orbitals, start in about -8 eV at G-point from the top of the valence band.…”
Section: H-terminated Dnwsupporting
confidence: 89%
“…Our results show that the closed-shell fully hydrogenated DNWs are non-magnetic materials. However, defects can induce magnetism in carbon allotropes [15]. We found that the local atomic magnetic moment may be induced in the DNWs if there is a free dangling bond on the surface that is not passivated by for example a hydrogen atom.…”
Section: Introductionmentioning
confidence: 86%
“…structural deformation or chemical functionalizations 4,5 . However, the only dispute that restrict the potential application of graphene in modern opto-electronic devices is its zero band gap nature 6,7 . Afterwards, a plethora of investigations have been performed on graphene in order to tune its band structure [8][9][10] .…”
mentioning
confidence: 99%
“…That gives rise to various important aspects of topological insulators [28]. The SOC effect is negligible for graphene while it is prominent for systems with large atomic number [29][30][31][32][33].…”
Section: Topological Phase and Associated Symmetriesmentioning
confidence: 99%